Priority effects are interactively regulated by top‐down and bottom‐up forces: evidence from wood decomposer communities. (4th July 2017) - Leopold, Devin R.; Wilkie, J. Paula; Dickie, Ian A.; Allen, Robert B.; Buchanan, Peter K.; Fukami, Tadashi
Abstract: Both top‐down (grazing) and bottom‐up (resource availability) forces can determine the strength of priority effects, or the effects of species arrival history on the structure and function of ecological communities, but their combined influences remain unresolved. To test for such influences, we assembled experimental communities of wood‐decomposing fungi using a factorial manipulation of fungivore ( Folsomia candida ) presence, nitrogen availability, and fungal assembly history. We found interactive effects of all three factors on fungal species composition and wood decomposition 1 year after the fungi were introduced. The strength of priority effects on community structure was affected primarily by nitrogen availability, whereas the strength of priority effects on decomposition rate was interactively regulated by nitrogen and fungivores. These results demonstrate that top‐down and bottom‐up forces jointly determine how strongly assembly history affects community structure and function.